EVALUASI FISIK KRIM ANTIINFLAMASI EKSTRAK KULIT BAWANG MERAH DENGAN VARIASI KONSENTRASI TRIETANOLAMIN DAN ASAM STEARAT - Nuraini, April; Puspitasari, Dianita Rahayu; Rokhani, Ratri (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Inflammation is the body's defense function against the entry of organisms and other disturbances. The drugs used often have an effect on gastrointestinal disorders, so other alternative treatments are being developed that can minimize side effects. The quarcetin content of shallot skin extract, which has anti-inflammatory activity, is formulated in a cream dosage form. The emulsifiers in the m/a cream formula are stearic acid and triethanolamine (TEA). This study aims to determine the physical evaluation of an anti-inflammatory cream containing shallot skin extract with variations in concentrations of TEA and stearic acid. The method used in this study is the experimental method. Formulations I, II, and III with varying concentrations of TEA and stearic acid (2:8%, 3:10%, and 4:12%) were used. Tests carried out included organoleptic tests, homogeneity, pH, spreadability, and adhesion. The cream formula passed the organoleptic test with a distinctive shallot smell, semi-solid form, brownish red color, all formulas were homogeneous, pH 5.264-6.417, spreadability 3.849-6.251 cm, and adhesion 83-132 seconds. Higher concentrations of TEA and stearic acid had an effect on adhesion and spreadability but had no effect on organoleptic properties, homogeneity, or pH. Onion skin extract cream with a concentration of TEA:2%:8% stearic acid gave the best physical quality.